Quranic Exegesis Studies in Malaysia: Realities, Challenges and Future Direction - Abdullah, Mustaffa; Gokaru, Shuaibu Umar; Abdul Hamid, Faisal @ Ahmad Faisal; Mohd Nor, Mohd Roslan (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2025)
The study of Quranic exegesis in Malaysia has witnessed significant developments. However, various challenges persist, particularly in the form of misinterpretations. Identifying these misinterpretations is crucial to fostering accurate understanding and addressing contemporary issues effectively. This research explores the current realities and challenges in Quranic exegesis in Malaysia, identifies the forms of misinterpretations, and anticipates future directions to ensure accurate and contextually relevant interpretations of Quranic verses. This study reviews prominent Malaysian exegetical works, such as al-Bayan Pada Ta’wil Ayat-Ayat al-Quran by Abdul Aziz bin Salam, Khulasah al-Qur’an by Maulana Noh, and Pedoman Muttaqin by Abdul Hayei Abdul Syukur. Additionally, it references classical and contemporary commentaries by Muslim exegetes, including Ibn Kathir, Al-Shawkani, Al-Tabari, Al-Maraghi, Ibn Atiyyah, and Tafsir al-Misbah by Muhammad Quraish Shihab. Using a qualitative library approach, the study identifies and analyzes data from relevant sources through thematic analysis. Key themes include deviant interpretations, material constraints, lack of expertise in exegesis, and the influence of social and political factors on Quranic studies. The findings reveal that the development of Quranic exegesis in Malaysia was initially influenced by the reformative efforts of al-Azhari scholars in Egypt, pioneered by Shaykh Muhammad Abduh and further advanced by his disciples, such as Shaykh Mustafa al-Maraghi and Sayyid Muhammad Rashid Rida. Exegetical studies in Malaysia encompass traditional, scientific, and thematic approaches. Despite these advancements, challenges remain, including the misuse of Quranic interpretations for political purposes and rational interpretations by social groups such as LGBT activists, feminist movements, and figures like Kasim Ahmad, who oppose the Prophet’s traditions (PBUH). These challenges stem from inappropriate methodologies, extreme ideologies, and rationalist perspectives that deviate from sound exegetical principles. This research concludes that an integrated and unified approach is needed to strengthen the methodologies of Quranic exegesis. Such efforts are essential to ensure interpretations that are not only accurate and relevant to contemporary contexts but also adhere to proper exegetical principles.